Three new Psammobiont species of Copidognathus (Acari, Halacaridae) from the Philippines - Bartsch, Ilse (1984)
In littoral service systems and sandy beaches in the Philippines, a rich halacarid fauna is living. In samples from Mactan Island, hitherto, 15 species of the genus Copidognathus were found. Three species- new to science- are described in this paper.
Includes bibliographical references (page 208) and index.
Keywords: Zoology; Copidognathus bunofer -- Description; Copidognathus festivus -- Description; Copidognathus mirus -- Description; Halacaridae